Performance and Capacity Analysis of Pabringan Road in The City of Yogyakarta - Dewi, Kemmala; Sidiq, Alif Lombardoaji; Nasirun, Achmad (International Journal of Engineering, Science and Information Technology, 2025)
This study aimed to ascertain the traffic volume, evaluate the performance and degree of saturation, and identify the service level category on Pabringan Road in Yogyakarta City. We surveyed to obtain primary data for the research method. We then analyzed the data using the Indonesian Road Capacity Manual 1997. According to the survey results, Pabringan Road experiences peak volumes of 792.1 pcu/hour in the morning, 979.3 pcu/hour in the afternoon, and 1103.3 pcu/hour at night. The road capacity calculation yielded a maximum capacity of 1185.52 pcu/hour. The speed on Pabringan Road decreased by 43.52% compared to the design flow speed of 23.72 km/hour, which was approximately 0.75. The analysis results indicate that during the morning peak hour, the level of service falls into category C, characterized by stable flow, increasing traffic density, and an increase in internal obstacles. During the afternoon peak hour, the service level falls into category D, indicating an approaching unstable flow and a high traffic volume. Changes in traffic flow conditions significantly impact the speed, even though it remains manageable. Moderate traffic density, fluctuations in traffic volume, internal traffic obstacles, and temporary obstacles can cause a significant speed reduction. High traffic interval obstacles significantly reduce traffic speed during the evening peak hour, causing drivers to experience short-duration congestion.